2010
DOI: 10.1507/endocrj.k10e-068
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of anti-islet autoantibodies in Japanese patients with type 1 diabetes

Abstract: Abstract. Circulating anti-islet autoantibodies in sera are used as a predictive marker for type 1 diabetes (T1D). We here report two Japanese patients with autoimmune thyroid disease complicated with T1D in whom the time course of anti-islet autoantibodies were observed before the clinical onset of diabetes. Case 1: A woman who had developed Graves' disease at age 25 was diagnosed with type 2 diabetes at age 31; six months later, insulin therapy was started. At age 36 she was diagnosed with T1D due to glutami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
1
0
1
Order By: Relevance
“…We searched PubMed and the Japanese Igaku-Chuo-Zassi database using a combination of the key words, “slowly progressive type 1 diabetes mellitus” and “gestational diabetes mellitus”. The characteristics of five patients, including the present patient, were consistent with SPIDDM following a diagnosis of GDM (Table 2) (32-34). The mean age of these patients was 34 years, and the mean BMI was 19.5 kg/m 2 , which was relatively low.…”
Section: Discussionsupporting
confidence: 57%
“…We searched PubMed and the Japanese Igaku-Chuo-Zassi database using a combination of the key words, “slowly progressive type 1 diabetes mellitus” and “gestational diabetes mellitus”. The characteristics of five patients, including the present patient, were consistent with SPIDDM following a diagnosis of GDM (Table 2) (32-34). The mean age of these patients was 34 years, and the mean BMI was 19.5 kg/m 2 , which was relatively low.…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, in longitudinal studies of genetically at‐risk children followed from birth, it has been reported that the presence of multiple anti‐islet autoantibodies greatly increases the probability for type 1 diabetes 25 , and IA‐2A and ZnT8A are shown to appear later, in general, during the subclinical disease process and to herald more rapid progression to type 1 diabetes than GADA 26,27 . These data imply that anti‐GAD response might be a sign of general autoimmunity, whereas IA‐2A and ZnT8A might be a surrogate indicator of residual β‐cell mass 28–30 , although there is a study showing that the prevalence of IA‐2A and ZnT8A at and after type 1 diabetes onset did not strongly correlate with endogenous insulin secretion 31 . To avoid autoimmune thyroid disease convoluting the results of the present study, we excluded the type 1 diabetic patients with autoimmune thyroid disease who were persistently positive for GADA 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Наиболее критичес-ким периодом для возникновения этого заболевания у детей считают возраст от 1 до 5 лет. Именно в этом возрасте отмеча-ют высокий титр аутоантител в крови [4]. Одновременное выявление у ребёнка дру-гих диабетогенных аллелей человеческого лейкоцитарного антигена (HLA), нали-чие инсулинзависимого сахарного диабе-та в семье ещё больше увеличивают этот риск [5].…”
unclassified